Rancang Bangun Sistem Informasi Pengelolaan Pengangkutan Sampah Berbasis Web - Putri Zhachilia Susanto; Dewi Fatmarani Surianto; Inez Sri Wahyuningsi Manguling; Sari Wulandari; Ivan Fadillah Akram (PT. Lontara Digitech Indonesia, 2023)
This study discusses a web-based waste management transportation information system that adopts effective waste management concepts and strategies with the principle of reduce, reuse, recycle (3R) as a priority in waste management. The purpose of this research is to enhance public participation in waste management by providing relevant information, services, and resources through a website. The main features of this system include the management of community data, waste data, personnel data, and transaction data. Black box testing was conducted to ensure that the system's functionality complies with the specified requirements. The results of the testing demonstrate that the system operates effectively and is ready for comprehensive utilization. By adopting information technology in waste management, this system has the potential to improve efficiency, effectiveness, and environmental awareness, thus contributing to addressing waste management challenges sustainably.